Enemies [compact disc, unabridged] : a history of the FBI - Weiner, Tim (Random House Audio, 2012)
Here is the hidden history of America's hundred-year war on terror. The FBI has fought against terrorists, spies, anyone it deemed subversive, and sometimes American presidents. The FBI's secret intelligence and surveillance techniques have created a tug-of-war between protecting national security and infringing upon civil liberties. It is a tension that strains the very fabric of a free republic.